THE EFFECT OF THIN CAPITALIZATION AND TUNNELING INCENTIVES ON TAX AVOIDANCE THROUGH TRANSFER PRICING PRACTICES - Metta Ciptaningtyas; Lin Oktris (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
Tax avoidance remains a critical issue in Indonesia’s taxation system, as it potentially undermines government revenue. This study examines the effect of thin capitalization and tunneling incentives on tax avoidance, with transfer pricing serving as an intervening variable. The research focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Using a quantitative approach, this study applies purposive sampling and obtains 265 firm-year observations. Data were analyzed using STATA version 19 through regression and mediation analysis to test the proposed hypotheses. The empirical results indicate that thin capitalization has a significant positive effect on tax avoidance, suggesting that higher debt reliance is associated with greater tax aggressiveness. Tunneling incentives are also found to significantly influence tax avoidance, reflecting the role of controlling shareholders in shifting profits. Furthermore, the mediation analysis reveals that transfer pricing partially mediates the relationship between thin capitalization and tax avoidance, as well as between tunneling incentives and tax avoidance. These findings highlight the importance of transfer pricing practices as a mechanism through which aggressive tax planning strategies are implemented. This study contributes to the literature on corporate taxation by providing empirical evidence from the energy sector in an emerging market context and offers insights for regulators in strengthening tax supervision and transfer pricing regulations.